PTSD symptom changes during Trauma-Focused Cognitive Behavioural Therapy (TF-CBT) in children and adolescents: a Single-Case Experimental Design study - Lieke H. Kooij; Irma M. Hein; Samantha Bouwmeester; Ramón J. L. Lindauer (European Journal of Psychotraumatology)
Introduction: Trauma-Focused Cognitive Behavioural Therapy (TF-CBT) is an evidence-based therapy for posttraumatic stress symptoms (PTSS) in children and adolescents. Nevertheless, drop-outs and limited effectiveness in individual and more complex cases remain a challenge. Detailed insight into individual symptom changes during therapy is missing. A Single-Case Experimental Design (SCED) is used to evaluate the changes and impact of the different modules of TF-CBT.Methods: A SCED study with repetitive baseline was conducted. The most prominent symptoms for each participant were assessed weekly throughout therapy. Standardized self-report questionnaires measured trauma, anxiety, depression, trauma-related cognitions, and parent–child interaction at six key points. Pre- and post-assessments were based on the clinician administrated interview. Session reports were used to evaluate the therapy's progress.Results and Discussion: Eight participants (ages 14–21) were included in the study. Graphical visualizations are presented of each individual symptom during the baseline and full course of the therapy (range = 20–70 weeks), alongside the corresponding standardized self-report. Most changes are seen during the narrative module, especially combined with the cognitive reprocessing and sharing module. A more severe or complex PTSD profile, needed more integration of coping skills and more sessions. For negative cognitions such as self-blame, cognitive reprocessing is necessary during the narrative. This SCED study provides a detailed insight in the therapeutic process of TF-CBT in a complex and heterogenous population.